Love, Despair, and Resiliency: Ovid’s Contributions to an Interactionist Analysis of Intimate Relations - Prus, Robert (Qualitative Sociology Review, 2013)
Ovid (Ovidius – Publius Ovidius Naso; 43 BCE-18 CE) is well known in classical studies and poetic circles for his insightful portrayals of heterosexual relations. However, his The Art of Love and related texts have received scant attention from those in the social sciences. Ovid’s writings on love may be best known for their advisory and entertainment motifs, but this same set of texts also provides an extended and comparatively detailed set of observations on heterosexual interchanges, as well as some remarkably astute analysis of interpersonal relations more generally. Developed within a symbolic interactionist frame (Mead 1934; Blumer 1969; Strauss 1993; Prus 1996; 1997; 1999), this paper gives particular attention to the processes by which people engage others in romantic contexts, make sense of their experiences with one another, deal with an assortment of third-parties, and manage wide ranges of related emotional sensations as they work their ways through aspects of the broader relationship process (from preliminary anticipations and initial encounters to terminations and re-involvements of relationships). It is in these respects that this paper considers the more distinctive ethnographic potential of Ovid’s depictions of love in the Roman classical era. As an instance of ethno-history, Ovid’s considerations of people’s involvements with love, sex, and romance, as well as the varying emotional states that people experience along the way, add some highly instructive cross-cultural and trans-historical dimensions to more contemporary, generic examinations of affective relationships. Using Ovid’s materials as an ethno-historical database with which to assess contemporary interactionist notions of “developing relationships,” this paper concludes with a consideration of the implications of Ovid’s works and contemporary interactionist studies for research on intimate relationships, emotionality, and influence work.